EVALUATING THE IMPACT OF SHARIAH-COMPLIANT BUSINESS PRACTICES ON CONSUMER TRUST AND MARKET GROWTH IN ISLAMIC FINANCIAL INSTITUTIONS - Aldriantara Sofyan; Avid Leonardo Sari; Iwan Setiawan (UIN Sunan Gunung Djati Bandung, 2024)
This study evaluates the impact of Shariah-compliant business practices on consumer trust and market growth in Islamic financial institutions. Shariah-compliant business practices are fundamental to Islamic finance, emphasizing ethical conduct, fairness, and transparency in all transactions. This research aims to explore how these principles influence consumer perceptions and contribute to the growth and stability of the market. This study, utilizing a literature review approach, examines the impact of Shariah-compliant business practices on consumer trust. The findings reveal that adherence to Shariah principles significantly enhances consumer trust, leading to increased customer loyalty and market expansion. Furthermore, the study identifies key factors that drive consumer trust in Shariah-compliant institutions, including the role of religious adherence, transparency, and ethical business practices. The implications of this research are critical for Islamic financial institutions aiming to strengthen their market position and foster long-term growth. By highlighting the importance of Shariah compliance in building consumer trust, this study provides valuable insights for policymakers, financial institutions, and stakeholders in the Islamic finance industry.